SYSTEM DESIGN IN PROMOTION EMPLOYEES PT. XYZ - Widia Astuty; Sapta Aji. Skom. MM (Jurnal Sistem Informasi, 1999)
PT. XYZ is a company that is engaged in printing where the company is the onlycompany that does not exist, which will be established by the authors. This companyonly covers about employee promotions.Promotion of employees is one aspect of human resource development in a company,where the appraisal made by the leaders never known the process. Therefore in thispaper, the authors attempt to computerize the process of promotion of fair andobjective.In the process of promotion of the author tried to use the tools to develop the system.The bantuyang tool used to design and develop a system of promotion within thecontext of this paper including diagrams, DED, ERD, FOD proposed andNormalization.With the existence of system development and system design is done, the writer triesto mengkomputerisasi data processing employee promotions is from the discussion inthis writing.